Determination of Volatile Organic Compounds in Fourty Five Salvia Species by Thermal Desorption-GC-MS Technique - HATIPOGLU, Seda Damla; ZORLU, Nihal; Dirmenci, Tuncay; GOREN, Ahmet C.; GÖREN, AHMET CEYHAN; Öztürk, Turan; Topcu, GÜLAÇTI; TOPÇU, GÜLAÇTI (My University, 2016)
Volatile organic compounds (VOC) from dried aerial parts (flowers, leafs, leafy branches and stems) of fourty five Salvia species, harvested from different regions of Turkey, were determined using thermal desorption technique coupled to gas chromatography-mass spectrometer (TD-GC-MS). Total percentages of the detected volatile organic compounds of the Salvia species ranged from 70.30 to 99.65%. Total yield of VOC was found to be highly variable among Salvia species, and the percentage of each component also exhibited high variation. While sesquiterpene hydrocarbons represented 0.90-45.02% of the volatile organic compounds, the others were found to be monoterpene hydrocarbons 0.00-32.25%, monoterpenoids 0.94-53.60%, sesquiterpenoids 0.00-31.45% and hydrocarbons and derivatives 2.99-46.87%. The rest of the composition consisted of diterpene alcohols, fatty acids, phenolics and triterpenes. In total, 108 volatile compounds were identified from studied 45 Anatolian Salvia species.